Biological Decolorization of Synthetic Dyes Textile Wastewater by Aspergillus niger: A Review: english - Prawitasari, Diah Ayu (Jurnal Sains & Teknologi Lingkungan, 2024)
The textile industry's wastewater is mainly comprised of synthetic dyes. Synthetic dyes are complex organic compounds that offer significant resistance to environmental conditions and highly harmful to ecological systems. The decolourization process can be enhanced by biological agents. The brown rot fungus, Aspergillus niger, is a biological agent with potential for the decolorization of synthetic colours. This article discusses information and literature review of investigations on the decolorization capacity of synthetic dyes by Aspergillus niger fungi. The literature review involved the analysis of qualitative data, observation, and the derivation of conclusions from previous research journals. The study's results demonstrate Aspergillus niger fungi significant potential of synthetic dye removal can up to 90% via simultaneous biodegradation and biosorption processes. Many variables effect the removal procedure, including pH, agitation settings, temperature, initial dye concentration, and nutritional content.